Economic policy change and women's employment in Township and Village Enterprises (TVE) : case study in Shanxi Province, China - Min, Tian; Kusakabe, Kyoko; Earth, Barbara; Swierczek, F.W.; Ford Foundation of International Fellowships Program (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
The Chinese Township and Village Enterprises (TVEs) is a unique type of rural enterprises in the world. Since 1979, China has carried out economic reform that result in TVEs experienced various changes in terms of the ownership, employment patterns and production structures. The most TVEs of Shanxi Province have carried out institutional transition to vary kinds of forms. This study aim to look at how the economic policies change affected TVEs woman workers employment in Shanxi Province. By interviewed 49 workers, employers and relevant people and collected 165 questionnaires at five enterprises in Shanxi Province, China, the results have been illustrated the changing of female and male workers employment situations during TVEs institutional transition. In general, the employment conditions in TVEs tend to be less favorable than those in the SOE sectors, thus, the nature of rural enterprises workers is often associated with lower wages, less job security and limited welfare of employment. So that, the study has also focus on the issues of female and male employment condition in terms of wages, labour protection, social interests, opportunity for work and access to skill. As the result, the survey shows the mainly changes that, the TVE institutional transition and privatizing has contributed to gender disparity at workplace. The mainly aspects are: first of all, the wage scheme changed from structure wage to station wage systems, result in women and men workers' wages' have increased significantly. However, the wage gaps were widened by gender disparity. Second, the working condition at physical aspects had improved during the TVEs institutional transition. However, there are engendering competitive pressures and reduced job security especially for woman workers. Third, there are more casual and short contract workers were used and most of them are women and the social securities for woman workers is inadequate and inefficiency under the social protection in the TVEs. Compared with before and after TVEs institutional transition of the surveyed TVEs, female and male workers employment situation have been changed which result in woman workers status have been changed at workplace, in society and family.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2006
Keywords: Women employees -- Economic aspects -- China -- Shanxi